Model-Based Analysis of Factors Influencing Solar Energy Efficiency: Dust Accumulation and Shading Effects - Tur, Mehmet Rida; Padmanaban, Sanjeevikumar; Hossain, Eklas; Al-Hajj, Rami; Wadi, Mohammed; Shobole, Abdulfetah; Wadi, Mohammed; Shobole, Abdulfetah Abdela (Institute of Electrical and Electronics Engineers Inc., 2024)
Solar energy is widely regarded as the most significant renewable energy source, with photovoltaic (PV) cells serving as the primary component for electricity generation from solar radiation. Several factors influence the energy production efficiency of PV cells, including but not limited to, radiation levels, temperature, cable losses, dust accumulation, and shading. These factors are often interrelated, where one factor can exacerbate the impact of another. In this study, various parameters affecting solar efficiency were examined by integrating them into a model, with each factor analyzed individually. Real system data was collected, and the impact of dust accumulation on the panels was assessed by measuring its contribution to shading, which in turn reduces the amount of radiation absorbed by the photovoltaic cells. The study anticipates that similar outcomes will be observed in large-scale applications, which could play a crucial role in shaping future investment decisions. It is suggested that optimizing the tilt angle of the panels and ensuring regular rainfall can effectively reduce dust accumulation, thereby enhancing the overall system efficiency.
Keywords: Dust Accumulation; Radiation; Shading Effects; Solar Energy